Interaction due to mechanical source in generalized thermo microstretch elastic medium - Kumar, Varun; Singh, R. (Zielona Góra: Uniwersytet Zielonogórski)
The eigen value approach, following the Laplace and Hankel transformation has been employed to find a general solution of the field equations in a generalized thermo microstretch elastic medium for an axisymmetric problem. An infinite space with the mechanical source has been applied to illustrate the utility of the approach. The integral transformations have been inverted by using a numerical inversion technique to obtain normal displacement, normal force stress, couple stress and microstress in the physical domain. Numerical results are shown graphically.
Keywords: generalized thermo-microstretch; eigen value; Laplace transform; Hankel transform; mechanical source